1990
DOI: 10.1111/j.1399-3038.1990.tb00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of atopic disease in relation to family history and cord blood IgE levels

Abstract: The cumulative incidence of atopic disease from birth to about 11 yr of age and the prevalence during the 11th year was investigated in a cohort of 1654 non‐selected children by an evaluated questionnaire. The total cumulative incidence of obvious atopic disease was 32. 5%, of bronchial asthma 5. 3%, and allergic rhinoconjunctivitis 14. 4%. The prevalence of itopic disease was 23. 7%. Obvious atopic disease developed in 67% of children with cord blood IgE ≥ 0.9 kU/l and a further 15% developed probable atopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
82
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 24 publications
6
82
1
Order By: Relevance
“…These studies are essen tially based on the use of lymphoprolifération assays, and only limited information is available on relevant T cell cyto kine responses over this age range. In particular, despite in-direct evidence of low-level fetal IgE synthesis [11] and of spontaneous production of high levels of Th2 cytokines by the fetoplacental unit throughout gestation [12], there is as yet no published evidence of allergen-speeific Th2 cytokine responses by human neonatal lymphocytes.…”
mentioning
confidence: 99%
“…These studies are essen tially based on the use of lymphoprolifération assays, and only limited information is available on relevant T cell cyto kine responses over this age range. In particular, despite in-direct evidence of low-level fetal IgE synthesis [11] and of spontaneous production of high levels of Th2 cytokines by the fetoplacental unit throughout gestation [12], there is as yet no published evidence of allergen-speeific Th2 cytokine responses by human neonatal lymphocytes.…”
mentioning
confidence: 99%
“…Several studies indicate that the prevalence of allergy is increasing, particularly in countries with a ''western lifestyle'' (1)(2)(3)(4)(5)(6). All of these studies were related to eczema or respiratory allergy, however.…”
mentioning
confidence: 99%
“…All of these studies were related to eczema or respiratory allergy, however. Less is known regarding the epidemiology of adverse reactions to food although such reactions are the major manifestations of allergy in infants and toddlers (6). A prospective study in Iceland yielded a prevalence of food allergy below 2% (Ardal, unpublished results).…”
mentioning
confidence: 99%
“…The possibility of the relationship between specific sensitization and cat ownership being influenced by families with atopic history keeping pets less frequently needs to be considered. However, this issue should not influence the results of the present study since it is repeatedly observed that in absolute numbers the majority of atopic patients do not come from families with a positive history but from "normal" parents [18,19].…”
Section: Discussionmentioning
confidence: 79%